Encruzilhadas imagéticas: o sagrado no terreiro - Santos, Talita Morais dos (2021)
The batuque has its own cosmology and characteristic sacred objects. Thus, this work aims to investigate the meaning attribution which relates to the sacred given by “saint-sons” to the sacred objects of spiritual affair by means of the photography which expresses them.The use of image, i.e., photography has been used as imagetic support for this research; during the living in the terreiro, as field, we try to understand the meaning of the sacred. This research is included in the research line 1, processes, knowledges and social practices, in the human sciences interdisciplinar post-graduation program. The methodologies chosen were the ethnographic intervention of participant research and ethnobiographic inspiration.